LDPC code and PPM modulation in free space optical communication system - Yang, Chuntao (Nanyang Technological University, 2020)
Free space optical (FSO) communication is a wireless technology, has many advantages that traditional microwave communication doesn’t have, such as no interference at the same frequency, wide bandwidth and convenient to use. Since it’s crucial problem has been solved, it’s now back to people’s sight to meet some special communication needs. Refer to a good amount of papers, this dissertation studied modeling of atmospheric channels; modulation and encoding methods that fit FSO systems; and simulated the transmission process. In modeling of atmospheric channels part, effects caused by atmosphere are investigated, which includes absorption, scattering and turbulence. Among them, turbulence is the most complicated, and also the most concerned. Based on learning atmospheric channels, several modulation methods are studied and compared. Pulse position modulation (PPM) has been used to do further study. Principles of LDPC code are investigated. PPM and LDPC code are used as modulation and encoding techniques to simulate the FSO system transmission. Performances of LDPC code are studied when transmitting data and images. Image processing method is proposed to improve image quality.